2012
DOI: 10.1530/eje-11-0494
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of acquired hypothyroidism: the Van Wyk–Grumbach syndrome

Abstract: The association in young females of long-standing primary hypothyroidism, isosexual precocious pseudopuberty and multicystic enlarged ovaries was first described in 1960 by Van Wyk and Grumbach. Since then, sporadic case reports have contributed to clarifying the key features of this syndrome. The unique elements that lead to this diagnosis are FSH-dominated sexual precocity combined with a delayed bone age in the presence of hypothyroidism. It is important to recognise this syndrome because initiating simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 37 publications
6
44
0
5
Order By: Relevance
“…The glycoproteins TSH, FSH, LH and hCG share a common alpha subunit but have a unique beta subunit that is specific to each hormone. They each act through transmembrane GPCRs to activate adenylate cyclase and stimulate c-AMP production 4 . Anasti et al 10 showed that recombinant human TSH elicited a dose-dependent response at the human FSH receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The glycoproteins TSH, FSH, LH and hCG share a common alpha subunit but have a unique beta subunit that is specific to each hormone. They each act through transmembrane GPCRs to activate adenylate cyclase and stimulate c-AMP production 4 . Anasti et al 10 showed that recombinant human TSH elicited a dose-dependent response at the human FSH receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In girls precocity menifests as breast enlargement, uterine bleeding and multicystic ovaries 3 . In 1960, Van Wyk and Grumbach first described a syndrome characterized by breast development, uterine bleeding and multicystic ovaries in the presence of long standing primary hypothyroidism 4 . Looking for hypothyroidism in girls with ovarian masses and precocious puberty is important in order to avoid surgery on the ovaries 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition is mostly manifested with ovarian cysts, early menstrual bleeding and galactorrhea in girls (1-3), while it is manifested with prominent penile enlargement and increased testicular size without increased testeosterone rarely in boys (4,5). Complete recovery is provided by administering thyroid hormone in both genders (6). In this article, we present an 8 year 9 month-old male patient who presented with short stature in whom increased testicular size found on physical examination directed us to the diagnosis.…”
mentioning
confidence: 99%
“…Increased prolactin levels can have an inhibitory effect on pituitary gonodotropins by slowing down the gonodotropin releasing hormone pulse frequency (7). In Van Wyk-Grumbach syndrome, luteinizing hormone levels are low or normal and follicle stimulating hormone levels are increased (3)(4)(5)(6). The mechanism of this is based on the interaction of common alpha subunits included in the structures of TSH and follicle stimulating hormone (8).…”
mentioning
confidence: 99%